Father-infant interactions and infant regional brain volumes: A cross-sectional MRI study. (December 2019) - Sethna, Vaheshta; Siew, Jasmine; Pote, Inês; Wang, Siying; Gudbrandsen, Maria; Lee, Charlotte; Perry, Emily; Adams, Kerrie P.H.; Watson, Clare; Kangas, Johanna; Stoencheva, Vladimira; Daly, Eileen; et al.
Abstract: Fathers play a crucial role in their children's socio-emotional and cognitive development. A plausible intermediate phenotype underlying this association is father's impact on infant brain. However, research on the association between paternal caregiving and child brain biology is scarce, particularly during infancy. Thus, we used magnetic resonance imaging (MRI) to investigate the relationship between observed father–infant interactions, specifically paternal sensitivity, and regional brain volumes in a community sample of 3-to-6-month-old infants (N = 28). We controlled for maternal sensitivity and examined the moderating role of infant communication on this relationship. T2-weighted MR images were acquired from infants during natural sleep. Higher levels of paternal sensitivity were associated with smaller cerebellar volumes in infants with high communication levels. In contrast, paternal sensitivity was not associated with subcortical grey matter volumes in the whole sample, and this was similar in infants with both high and low communication levels. This preliminary study provides the first evidence for an association between father-child interactions and variation in infant brain anatomy.